Analysis of Risk Factors that Influence the Lumbago Event in Hand-Rolled Clove Cigarette Workers at Margantara Jaya Cigarette Factories - Dewi Zuniawati; Indasah Indasah; Prima Dewi Kusumawati (Journal for Quality in Public Health, 2020)
Background: Lumbago or low back pain (LBP) is one of the musculoskeletal disorders, it is the result of incorrect ergonomics. Back pain is a problem in many countries, because it often affects productivity of the work. World Health Organization (WHO) estimates that the incidence of low back pain reaching 60-70% occurs in early adulthood. Purpose: The purpose of this study was to analyze of working period, the length of sitting, and sitting position in lumbago event and look for the most dominant factors among the three variables at Margantara Jaya Tulungagung Cigarette Factory. Methodhs: The study design used quantitative research as the research design by using a “cross sectional” approach. The sampling technique was used by the researcher was Simple Random Sampling with a sample calculation formula obtained a sample of 135 respondents. The data analysis techniques were using the Logistic Regression test. Results: The result showed that from 135 respondents who had been studied by the researcher, it was found that 115 respondents (85%) had positive lumbago. 80 of 135 respondents (59%) had more than 10 years of service, and 114 of 135 respondents (84%) sat for more than 9 hours per day and 122 of 135 respondents (92%) were in ergonomic sitting position. Based on the Logistic Regression test based on the omnibus test of the model, it showed a significance value of p-value = 0,000 <α = 0.05, it meant that H0 is rejected and H1 is accepted, this means that there was a joint effect between the factors of work period, length of work and sitting position of lumbago incidents in hand- rolled clove cigarette workers. Based on the value of Exp (B) with the highest value Exp (B) = 187,663 it can be concluded that the most dominant factor that affecting the lumbago event is the sitting position. Conclusion: There is a relationship between the factors of work period, length of work and sitting position of lumbago incidents in hand- rolled clove cigarette workers and the most dominant factor that affecting the lumbago event is the sitting position.